Developing a STEM-based students’ worksheet building material in elementary school Bandar Lampung City - Roni Agus Saputra; Herpratiwi Herpratiwi; Caswita Caswita (Jurnal Prima Edukasia, 2020)
This study aims to produce students’ worksheet-based STEM building material in elementary schools Bandar Lampung City. This type of research is research and development (Research and Development/ RD). The main steps in this research and development are (1) information gathering and preliminary research; (2) planning; (3) product development; (4) limited testing, and (5) final product revision. The population in this study was the fifth-grade educators of SD Negeri Langkapura District Korwil III. The sampling technique used was the purposive sampling technique. The research sample was 3 (three) fifth-grade teachers of SDN 3 Langkapura, SDN 2 Langkapura, and SDN 1 Langkapura. Data collection techniques using observation and questionnaires. The data analysis technique in this study was using qualitative descriptive analysis techniques. Based on the results of research and discussion, it can be concluded that the development of STEM-based LKPD building material in elementary schools Bandar Lampung City is very feasible to use in learning. This is based on the results of the validation of material experts at 92.75%, the results of the validation of design experts at 82.08%, and the results of the test to the teacher at 93.04%. This research is limited to the expert and practitioner test. It would be better if it was perfected in the effectiveness and attractiveness test.